Healthcare workers’ challenges in managing disease outbreaks: a systematic review from an Islamic perspective - Ahmad, Zeti Azreen; A.Manaf, Aini Maznina; Buyong, Mazni; Samsudin, Sofiah; Sawari, Mohd Fuad; Ahmad Yusof @ Hanafi, Hanani (IIUM Press, 2025)
Healthcare workers (HCWs) are prone to be at risk to health and safety hazards, particularly during disease outbreaks. This study examined the challenges confronted by HCWs in providing care and service during disease outbreaks. A systematic literature review (SLR) was adopted as the main approach of this study. A total of 61 articles were retrieved from two databases, Scopus and Web of Science, and analysed. Knowledge deficit and communication issues were identified as among the major challenges confronted by HCWs during disease outbreaks. These challenges were later analysed from an Islamic perspective by examining the responses provided in the Qur’ān and Ḥadīths. This study puts forward relevant Islamic guidelines on dealing with challenges during a disease outbreak that have been scarce in the literature. The study received approval from the IIUM Research Ethics Committee (IREC). It is also part of a research project on preventing and controlling disease outbreaks, as well as dealing with emergencies, funded by the Islamic Advisory group (AIG)